Incidence of Metabolic Syndrome and Its Risk Factors among Type 2 Diabetes Clinic Attenders in Isfahan, Iran. (15th March 2012) - Janghorbani, Mohsen; Amini, Masoud
Abstract : Aim . At present, little data exist about incidence and the risk factors associated with metabolic syndrome (MetS) in patients with type 2 diabetes mellitus (T2DM). The objectives of present study were to assess the incidence and risk factors of MetS in people with T2DM. Methods . During the mean (SD) follow-up period of 11.7 (4.8) years, 3, 047 patients with T2DM and free of MetS at baseline have been examined to determine incidence and predictors of progression to MetS. A modified the National Cholesterol Education Program—Adult Treatment Panel III definition with body mass index (BMI) instead of waist circumference was used for the MetS. Results . The prevalence of MetS was 63.2% (95% CI: 62.3, 64.1). The incidence of MetS was 28.5 (95% CI: 26.8, 30.2) (25.9 men and 30.9 women) per 1, 000 patient-years based on 35, 677 patient-years of follow-up. Multivariate analysis revealed that higher BMI and education, lower HbA 1 c and treatment with oral agent or insulin were associated with MetS. Conclusion . These are the first estimate of incidence and risk factors of MetS in patients with T2DM in Iran. These findings showed that the natural course of MetS is dynamic. The clinical management of patients with T2DM will contribute significantly to MetS prevention.